A zero-one goal programming model to use financial resources. Issue 1 (2nd January 2016) - Choi, Donghyun
Abstract : Supplier selection is a multi-criteria decision-making process. Suppliers should decide which resources to invest in with limited resources. Goal programming can support this decision-making process. Thus, this study used a case study to show this process by applying goal programming.